Fecal Multidimensional Assay for Non-Invasive Detection of Colorectal Cancer: Fecal Immunochemical Test, Stool DNA Mutation, Methylation, and Intestinal Bacteria Analysis - Mo, Shaobo; Wang, Hui; Han, Lingyu; Xiang, Wenqiang; Dai, Weixing; Zhao, Pengfei; Pei, Fengchun; Su, Zhixi; Ma, Chengcheng; Li, Qi; Wang, Zhimin; Cai, Sanjun; et al. (Frontiers in Oncology, 2021)
Background Fecal immunochemical test (FIT), DNA mutation, DNA methylation and microbial dysbiosis all showed promising in colorectal cancer (CRC) non-invasive detection. We assessed CRC detection with an assay combining all these strategies and investigated the effect of clinical features on the performance of this comprehensive test. Methods We performed a multi-dimensional analysis study using stool samples collected from 108 patients with CRC, 18 patients with colorectal adenoma, and 36 individuals with no evidence of colorectal disease. The multi-dimensional analysis of stool samples including FIT, stool DNA (sDNA) tests for 3 methylated genes (Septin9, NDRG4, BMP3) and 3 mutated genes (KRAS, BRAF, PI3KCA) using next generation sequencing as well as detection of stool bacteria level of Fusobacterium nucleatum and Parvimonas micra using qPCR method. We used a linear support vector classification model to analyze the data. Results The sensitivity of FIT alone was 69.4% for CRC and 11.1% for adenoma. Separately, the sensitivity of the detection of intestinal bacteria, DNA mutation and DNA methylation for CRC was 58.3%, 50.0% and 51.9%, respectively. The combination of FIT and sDNA tests had a sensitivity of 81.5% for CRC (AUC: 0.93, better than FIT alone, P=0.017) and 27.8% for adenoma with 94.4% specificity. Sensitivity of the multi-dimensional test to detect CRC with stage II (84.6%) and III (91.9%) CRC was relatively higher (88.2%) than that of patients with stage I (60.0%) and stage IV (75.0%) (P=0.024). The rate of CRC detection increased with tumor size (P=0.008) and age (P=0.04). Interestingly, the rate of CRC detection was higher in smoking persons than non-smokers with marginal significance (P=0.08). Conclusions The multidimensional assay of stool samples combining FIT and stool DNA tests further improved the diagnostic sensitivity for CRC. This could provide new approach for improvement of CRC screening and further demonstrations are warranted.